Use of a Purse-String Suture to Reduce Skin Graft Requirements - McCue, Jonathan; Kalliainen, Loree K. (Annals of surgical oncology, 2018)
Background When a wound cannot be closed in a linear fashion and either a local flap or skin graft is needed, a purse-string suture can be a useful adjunct to wound closure. Local tissue architecture is maintained in cases where clear surgical margins have not been achieved at the time of extirpative skin cancer surgery. We hypothesized that this technique could be applied to a range of wound sizes and locations to avoid or reduce the need for skin grafting. Methods We applied a non-absorbable purse-string suture to wounds in 18 patients over a 15-month period and measured the defect size before and after application of the suture intraoperatively. Residual defects were covered with full- or split-thickness skin grafts. Postoperative wound area, scar hypertrophy, partial graft loss and dehiscence following suture removal were additional outcomes. Results Ten patients achieved primary wound closure with the purse-string suture, while additional skin grafting was required in eight patients. Wounds closed primarily did not re-expand. Skin-grafted subjects had a 53.8% intraoperative wound area reduction but the skin grafts expanded during recovery, and ultimate reduction diminished to 11% on late follow-up. Wounds accounting for this late re-expansion were located on the extremities. Conclusions Purse-string sutures are helpful for wound closure in wounds that cannot be closed primarily. They can decrease the size of a skin graft if the wound cannot be closed completely. Wound re-expansion, particularly in extremity defects, may occur following early removal of the tension-bearing purse string.